The Role of Interpersonal Intelligence in Mediating The Influence of Character Strengths and Emotional Intelligence on Juvenile Delinquency - Lumangkun, Jimi; Mukhlis, Ahmad; Permana, Angrian (CV. Tripe Konsultan, 2024)
Juvenile delinquency is a crucial issue faced by many schools, including vocational high schools in Cilegon City. This study aims to explore the role of interpersonal intelligence in mediating the influence of character strength and emotional intelligence on juvenile delinquency. Using a quantitative survey method, data were collected from 250 vocational high school students in Cilegon City through a validated questionnaire and analyzed using the SEM-PLS approach. The results showed that character strength has a negative and significant effect on juvenile delinquency with a coefficient value of -0.321, indicating that increasing character strength can significantly reduce the level of juvenile delinquency. In addition, emotional intelligence also showed a negative and significant effect on juvenile delinquency. This confirms that increasing emotional intelligence also contributes to reducing juvenile delinquency. Interpersonal intelligence itself has a negative and significant effect on juvenile delinquency with a coefficient value of -0.161, indicating that better interpersonal skills can reduce the tendency of delinquent behavior. Furthermore, character strength and emotional intelligence were found to have a positive and significant influence on interpersonal intelligence, with coefficient values ​​of 0.370 and 0.484, respectively. Another important finding is the significant negative indirect effect of character strength and emotional intelligence on juvenile delinquency through interpersonal intelligence. This indicates that increasing character strength and emotional intelligence can reduce juvenile delinquency by increasing their interpersonal intelligence. This study concludes that strengthening students' character and emotional intelligence, as well as increasing interpersonal intelligence, are important strategies in reducing juvenile delinquency.